(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical and paraclinical characteristics of tuberculous meningitis in children at the Tropical Diseases Center, National Children’s Hospital. Subjects and methods: Cross-sectional descriptive study of 50 children from 1 month to 15 years old diagnosed and treated for tuberculous meningitis at the Center for Tropical Diseases, National Children’s Hospital. Results: Among the 50 children participating in the study, the common clinical manifestations were fever (94%), cough (42%), nausea/vomiting (54%), headache/irritability (48%), impaired consciousness (76%), cranial nerve palsy (22%). Cerebrospinal fluid: clear (50%), yellow and golden (37.5%), turbid (12.5%). Protein increased > 1 g/l (60.3%), glucose < 2.2 mmol/l (71.9%), median cell counts is 126 (57-392) cells/ml, of which cell count > 100 (54.7%), lymphocyte content > 50% (67.2%). Blood test: slightly increased white blood cell count, median value is 14.3 G/l, mild anemia, median hemoglobin is 105 g/l, platelet count is within normal limits. CRP index is slightly increased, median value is 10.4 mg/l. CT scan/MRI results show 86% abnormalities, including ventricular dilatation (68%), increased meningeal enhancement (66%), cerebral infarction (14%). Conclusion: Clinical features of tuberculous meningitis in children are not specific. Cerebrospinal fluid is usually clear with several hundred cells, in which lymphocytes predominate. Leukocyte count and CRP index are slightly increased, mild hypochromic anemia and hyponatremia are common. Ventricular dilatation and increased meningeal enhancement are common signs.